The design of hybrid work for improved employee engagement and well-being: perspectives for HRD practice - Nagori, Roopa; Lawton, Natalia Rocha (International Journal of Human Resource Development Practice Policy & Research, 2024)
Although hybrid work has increased and is here to stay, organizations are still experimenting with the design and the appropriate interventions required. Evidence is emerging that the well-being and employee engagement of staff has declined in hybrid work and it is necessary to understand this as a critical priority for HRD professionals. This study explores the key factors influencing the design of hybrid work for improved well-being and staff engagement through a systematic synthesis of the literature involving 78 empirical, conceptual or theoretical studies. The study identifies five distinct factors followed by key propositions for practice that offer recommendations around the following areas: A well-equipped space with appropriate workplace and time flexibility, culture and leadership development through communication and collaboration mechanisms, allocation of jobs, and tasks to prevent stress and the networks and tools to promote staff collaboration. Adequate training and interventions to avoid technostress and burnout due to digital workloads are essential for improved well-being. The article draws on international evidence to propose guidelines for designing hybrid work models. However, most evidence comes from the United States, the United Kingdom, and the European Union. In the future, exploring other contexts and offering a more universal framework for hybrid work would be beneficial.